2019
DOI: 10.3758/s13415-019-00729-9
|View full text |Cite
|
Sign up to set email alerts
|

Mapping articulatory and grammatical subcomponents of fluency deficits in post-stroke aphasia

Abstract: Fluent speech production is a critical aspect of language processing and is central to aphasia diagnosis and treatment. Multiple cognitive processes and neural subsystems must be coordinated to produce fluent narrative speech. To refine the understanding of these systems, measures that minimize the influence of other cognitive processes were defined for articulatory deficits and grammatical deficits. Articulatory deficits were measured by the proportion of phonetic errors (articulatory and prosodic) in a word … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 61 publications
(92 reference statements)
0
19
0
Order By: Relevance
“…Ferreira, 1993). Although our analysis of connected speech did not quantify deficits at a phonological level of specificity, the postcentral and SMG foci we identified are similar to damaged regions associated with phonological and phonetic errors during picture naming by speakers with chronic stroke (Mirman et al, 2019). Damage to the left IFG and insula was associated with deficits producing words with grammatical functions and nearby regions were also associated with reduced syntactic accuracy.…”
Section: Lexically-driven Vs Syntactically-driven Stages Of Productionmentioning
confidence: 73%
See 3 more Smart Citations
“…Ferreira, 1993). Although our analysis of connected speech did not quantify deficits at a phonological level of specificity, the postcentral and SMG foci we identified are similar to damaged regions associated with phonological and phonetic errors during picture naming by speakers with chronic stroke (Mirman et al, 2019). Damage to the left IFG and insula was associated with deficits producing words with grammatical functions and nearby regions were also associated with reduced syntactic accuracy.…”
Section: Lexically-driven Vs Syntactically-driven Stages Of Productionmentioning
confidence: 73%
“…This study demonstrated neuroanatomical and functional divisions within grammatical encoding during connected speech which dovetail with existing neurobiological sentence production evidence. In chronic stroke speakers, LBM analysis demonstrated that reduced numbers of words produced in sentences during story-telling was associated largely with damage to the left IFG with smaller foci in the postcentral gyrus and IPL (Mirman et al, 2019). When speakers undergoing awake craniotomies described pictures depicting actions, direct cortical stimulation of the pars opercularis and triangularis of the LIFG resulted in 50 % of patients producing grammatical errors during sentence production (Chang et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Consequently, they risk masking relevant variation in performance across the relevant domains. In contrast, approaches that explore individual cognitive domains have great potential to improve our understanding and prediction of cognitive health and pathology (Barch & Ceaser, 2012;Covey et al, 2011;Rivera-Fernández et al, 2021), and have been effectively applied to predict performance in various populations, including dementia (Hackett et al, 2018;Rivera-Fernández et al, 2021) stroke aphasia (Butler et al, 2014;Mirman et al, 2019) and healthy aging (Reddy et al, 2015). We therefore considered a wide range of behavioural measures from the HCP dataset, and PCA analysis revealed four components underpinning performance on these cognitive tasks: retention and retrieval, processing speed, self-regulation, and encoding processes.…”
Section: Cognitive Domainsmentioning
confidence: 99%